The Relationship between Non-financial Factors, Capital Structure and the Performance of the Listed Companies on the Stock Exchange - Bakhshani, Safiye (International Journal of Economics and Financial Issues, 2017)
Capital structure is considered to be the most important parameter affecting the valuation of companies and their orientation in the capital markets. Companies in a similar industry are expected to employ fairly similar policies and strategies for financing and determining their own capital structure since they have the same activities as well as internal and external factors affecting them. Accordingly, the present study investigated the impact of the industry type and the company age on the capital structure and the impact of capital structure on the financial performance of 203 companies listed on the Stock Exchange. Finally, the financial ratios of 1007 institution-year in 27 industry codes were evaluated. The structural equation modeling was employed to test the hypothesis using PLS software. The results showed that there is no significant relationship between industry and the capital structure. However, there is a significant relationship between the age of the institution and the ratio of debt to equity at the level of P-Value = 0.05. Moreover, no significant relationship was seen between the capital structure and the performance at the level of P-Value = 0.05. Keywords: financial factors, non-financial factors, capital structure, company performance JEL Classifications: G2, G3